ENHANCE A DESIGN AND MANAGEMENT ONE STOP GAS STATION TEBING TINGGI CITY - Adhita Nugraha Mestika (Jurnal Ekonomi, 2022)
The city of Tebing Tinggi was currently has reformed to become a metropolitan city after the city of Medan in North Sumatra. The high mobility of the population makes the transportation system very important. At present the growth of transportation modes is so rapid, once of the important things in this mode of transportation is the fuel station Pabatu, Padang Hulu, Tebing Tinggi, Kutha Tebing Tinggi, Sumatra Lor. maximum use of gas.